Being Passionate to Perform: The Joint Effect of Leader Humility and Follower Humility - Diao, Huiyue; Song, Lynda Jiwen; Wang, Yue; Zhong, Jun (Frontiers in Psychology, 2019)
Although humility is an outstanding characteristic of many beloved and respected leaders, little is known regarding the effect of leader humility on follower job performance. The current study examines how leader humility affects follower performance. Drawing on the self-determination theory, we suggest that leader humility, via follower harmonious passion, contributes to follower performance. With multiphase leader-follower paired data, we find that leader humility is positively related to follower performance, this positive relationship is partially mediated by follower harmonious passion, and the indirect effect of leader humility on follower performance via follower harmonious passion is stronger with a high level of follower humility.